Cultivation at the Imperial College, Trinidad - (:unkn) unknown (Davidson and Todd Ltd., Trinidad, 2010)
The postcard shows rows of cultivated agricultural crops at the Imperial College of Tropical Agriculture (ICTA) and at far left, one of the College's houses. ICTA, orignally called the Agricultural College of the West Indies, was renamed in 1923. After several mergers it became the Faculty of Agriculture of the University College of the West Indies which became The University of the West Indies after receiving its charter in 1962, the year of Trinidad and Tobago's independence. This used postcard is addressed to Miss Gladys Smith of New Jersey, United States of America. The card is postmarked 22 March 1943 and affixed are two Trinidad and Tobago postage stamps: a twenty-four cents and a six cents.
Colour: Sepia (print); Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Universities and colleges--Trinidad and Tobago; 1943; Agricultural colleges--Trinidad and Tobago; Crops--Trinidad and Tobago; Imperial College of Tropical Agriculture; ICTA